What make intention halal food consumption? Study on Turkey’s consumers’ perspective - Haque, A. K. M. Ahasanul; Tor-Kadioglu, Cansu; Md Humayun Kabir, Sardar (Psychology and Education, 2021)
The study purposes to investigate the factors that influence Muslim consumers’ purchase behaviour on halal food products in Turkey. Based on the extended TPB model; halal food awareness among Muslim consumers, their religious level, social factors, intention to purchase and actual behaviour towards halal food products are investigated. 152 valid responses were obtained using online survey method. Confirmatory factor analyses were performed to ensure reliability and content validity. A structural equation modelling technique was performed to test the hypotheses among variables. It has been understood that the intention to purchase halal food has an effect on the behavioral intention of consumers. Besides, it was understood that the awareness of halal food was not affected by the level of religiosity, and that social factors were effective in awareness of halal food. First, some respondents were unwilling to respond to survey due to the sensitivity of religious issues. Secondly, the sample of the research was limited to Turkey. A comparative study would be desirable between other Muslim countries. This study contributes to the literature and sectoral inferences can be made.